Механізм управління концентрацією та укрупненням капіталу як складова системи управління конкурентоспроможністю великих промислових підприємств - Верескун, М.В. (Економіка промисловості, 2012)
Запропоновано комбінований підхід до управління процесами концентрації та укрупнення капіталу. Розроблено двоконтурний організаційно-економічний механізм управління цими процесами, використання якого дозволить великим промисловим підприємствам постійно підтримувати необхідний рівень конкурентоспроможності за рахунок придбання нових активів чи збереження існуючих від рейдерських атак.
Ключові слова: концентрація капіталу, система управління конкурентоспроможністю, організаційно-економічний механізм, промислові підприємства. Предложен комбинированный подход к управлению процессами концентрации и укрупнения капитала. Разработан двухконтурный организационно-экономический механизм управления этими процессами, использование которого позволит крупным промышленным предприятиям постоянно поддерживать необходимый уровень конкурентоспособности за счет приобретения новых активов или эффективной защиты существующих от рейдерских атак.
Ключевые слова: концентрация капитала, система управления конкурентоспособностью, организационно-экономический механизм, промышленные предприятия. In the current conditions of the market economy and its globalization and increased competition in all markets one of the most important ways to improve the competitiveness of companies is consolidation and concentration of capital. Using the concentration and consolidation of capital as a tool to enhance competitiveness, the company plans to achieve the goal in many ways, but the main and the most well-known are: economies of scale and achieve synergies. In terms of strategic development , the most modern companies have a section devoted to the possible mergers and acquisitions as the primary form of the processes of concentration and consolidation of capital.
On the other hand, we know that over 60% of all mergers are unsuccessful, do not justify the expectations of managers and owners of businesses, and generate losses. In 70% of cases potentially winning trades losing are the poor quality of training and the integration. Therefore, the management of the process of concentration and consolidation of capital in industry is highly relevant.
The paper developed a combined approach to the management of concentration and consolidation of capital, which consists of a combination of system and process-based management approaches. The main advantages of the proposed approach consist in the possibility of a synergistic effect due to coordination of all elements of the process in space and time, detailing the main elements of the process, improving controllability management process at the most appropriate levels. Combined approach develops double-organizational-economic mechanism of management of concentration and consolidation of capital, which consists of blocks of goal-setting and active and passive circuits. Each circuit is independent of the other and can work both separately and in parallel with the other. The effectiveness of the management process is not reduced under any operation mechanism. Despite the fact that these paths are independent, their structure is formed from the same set of features in the eastern parts: analytical, process and evaluation.
Using the developed mechanism in the management of large industrial enterprises competitiveness will allow them to continuously analyze the market situation and, in favorable conditions, purchase new assets in the market, and defend existing assets from raider attacks.
Keywords: concentration of capital,the system of management of competitiveness, organizational and economic mechanism, industrial enterprises.